Niraparib Enhances and Synergizes with Ganglioside GD2 to Potentiate its Inhibitory Effect on Bladder Cancer Cells - Lu, Shan; Gao, Xiaojia; Li, Xin; Zhao, Hongchao; Lu, Hongda (Combinatorial Chemistry & High Throughput Screening, 2025)
AimThis study aimed to study the inhibitory effect of niraparib alone or in combination with GD2 specific antibody on Bladder Cancer (BCa).MethodsThe migration ability of BCa cells was assessed through a scratch assay. CCK-8 assay was performed to evaluate the viability of BCa cells, and Transwell invasion assays were utilized to examine invasive capacity. The expression levels of E-cadherin and vimentin in BCa cells were measured using QRT-PCR.ResultsWestern blot showed the EMT level to be the lowest in the niraparib+GD2 group. The transwell invasion assay suggested that the invasion ability of BCa cells was weakened in the niraparib+GD2 group. CCK8 assay indicated that the proliferation ability of BCa cells was decreased. Scratch test suggested that the migration ability of BCa cells was weakened. PCR result showed that the niraparib + GD2 group had the most significant inhibitory effect on mRNA expression of EMT markers.ConclusionNiraparib combined with a GD2-specific antibody exerted a more prominent inhibitory effect on BCa.
Keywords: Niraparib